THE EFFECT OF E-WOM IN INSTAGRAM ON TRUST AND PURCHASE INTENTION TO MOUNT DAGO, BOGOR - Andrianto, Nizam Mohammad; Diposumarto, Ngadino Surip; Farradia, Yuary (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
Information spreads rapidly through social media, especially as the number of social media users in Indonesia continues to increase yearly. This is an essential concern for managers of tourist destinations, especially in terms of purchasing interest, which has also increased in recent years. Information disseminated between social media users commonly referred to as e-WOM is thought to influence travel purchase intention. Therefore, the researcher intends to see the extent to which e-WOM on Instagram affects Trust and interest in purchasing tours to Mount Dago, Bogor. This research is quantitative research with explanatory research methods. The sampling technique used in this research is non-probability sampling with accidental sampling technique, where the respondents in this study are visitors to Mount Dago who use Instagram and are interested in visiting Mount Dago. This questionnaire was distributed via Google Forms, then the data was processed using SmartPLS 3. Of the 120 respondents, the results showed that the effect of the e-WOM variable on Purchase Intention is significant because the t-statistic value> 1.96, which is 11,357> 1.96. This means that the e-WOM variable affects Purchase Intention. Meanwhile, the Trust variable significantly affects Purchase Intention, indicated by the t-statistic value> 1.96, which is 7,280> 1.96. This means that Trust has a significant influence on Purchase Intention. This research provides important implications for tourism managers of Mount Dago to manage e-WOM information on social media well to increase consumer trust and encourage their purchase interest